1998
DOI: 10.1063/1.122273
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optically active E1 transversal optic phonon modes in AlxGa1−xN layers deposited on 6H–SiC substrates using infrared reflectance

Abstract: We report an investigation, performed in the full composition range x=0–1, of the change in infrared reflectivity spectra of AlxGa1−xN layers deposited on 6H–SiC substrates. We have found two different transverse E1(TO) phonon frequencies that can be assigned to AlN-like and GaN-like modes. The composition dependences of these frequencies can be well approximated by linear functions and the oscillator strengths scale like the corresponding Al and Ga mole fractions, respectively. On a purely experimental basis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
30
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 16 publications
6
30
0
Order By: Relevance
“…The main concern here is with the Fro È hlich interaction involving the LO modes in an alloy. This has been discussed by Swierkowski et al [4] and Nash et al [5], and the approach of the latter work is followed to describe LO modes in wurtzite Al x Ga 1± ±x N. It is found that, in fact, the alloy exhibits two-mode behaviour but that the Fro È hlich coupling associated with the lower frequency mode is extremely weak, making the alloy virtually a one-mode alloy as far as LO polar coupling is concerned, in agreement with Wisniewski et al [12].…”
supporting
confidence: 67%
“…The main concern here is with the Fro È hlich interaction involving the LO modes in an alloy. This has been discussed by Swierkowski et al [4] and Nash et al [5], and the approach of the latter work is followed to describe LO modes in wurtzite Al x Ga 1± ±x N. It is found that, in fact, the alloy exhibits two-mode behaviour but that the Fro È hlich coupling associated with the lower frequency mode is extremely weak, making the alloy virtually a one-mode alloy as far as LO polar coupling is concerned, in agreement with Wisniewski et al [12].…”
supporting
confidence: 67%
“…[2][3][4][5][6][7] In contrast, the knowledge of the SPP mode of the Al x Ga 1−x N alloy remains unclear or unexplored. For its constituents, the study of the SPP mode is also rarely reported and has not received sufficient attention.…”
mentioning
confidence: 86%
“…Numerous studies have employed Raman scattering and far-infrared ͑IR͒ spectroscopies to investigate several physical properties of GaN, AlN, and the ternary alloy AlGaN such as their phonon modes, the crystal quality and the orientation of the as-grown material, free-carrier effects, and the piezoelectric response. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] It is now clear that the longitudinal optic ͑LO͒ phonons ͓A 1 ͑LO͒ and E 1 ͑LO͔͒ of hexagonal AlGaN display a one-mode behavior, whereas the rest of the Raman or IR active phonon modes ͓E 2 , A 1 ͑TO͒ and E 1 ͑TO͔͒ exhibit a two-mode behavior. 13,17 Similarly, it has been shown that the LO and transverse optic ͑TO͒ phonons of cubic AlGaN exhibit one-mode and two-mode behaviors, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6][7][8][9][12][13][14][15] In contrast, only a few works reported IR transmission measurements, 3,9,12,18 most of which were performed in normal-incidence configuration. Reports dealing with oblique-incidence IR transmission to study the phonons of group-III nitrides are scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation